Assessment of CMIP6 Model Performance for Wind Speed in China - Zhao, Lijun; Jin, Shuanglong; Liu, Xiaolin; Wang, Bo; Song, Zongpeng; Hu, Ju; Guo, Yuyang (Frontiers in Climate, 2021)
As the major renewable energy, wind can greatly reduce carbon emissions. Following the “Carbon Neutral” strategy, wind power could help to achieve the realization of energy transformation and green development. Based on ERA5 reanalysis data and the multi-ensemble historical and scenario simulations of the Coupled Model Intercomparison Project Phase 6 (CMIP6), a variety of statistical analysis are used to evaluate the performance of CMIP6 simulating the wind speed in China. The conclusions are as follows: spatial patterns of the nine CMIP6 models are similar with ERA5, but BCC-CSM2-MR and MRI-ESM2-0 highly overestimate the wind speed in Northwest China. CESM2-WACCM, NorESM2-MM and HadGEM3-GC31-MM behave better than the other six CMIP6 models in four specific regions and are chosen for detailed study. CESM2-WACCM, NorESM2-MM and HadGEM3-GC31-MM tend to simulate a larger wind speed than ERA5 except the yearly averaged wind speed in region Ⅱ and region Ⅳ. CESM2-WACCM and NorESM2-MM simulate a large monthly mean wind speed but the value is relatively close with ERA5 in the summer. HadGEM3-GC31-MM overestimates wind speed in region I and region Ⅱ from April to October, but gets closer with ERA during winter. CESM2-WACCM, NorESM2-MM and HadGEM3-GC31-MM simulate an increasing trend in Tibetan Plateau and Xinjiang in the next 100 years, while NorESM2-MM projects rising wind speed in the eastern part of Inner Mongolia and HadGEM3-GC31-MM simulates increasing wind speed in the Northeast and central China. The future wind speed in three models is projected to decline in region I and the value of HadGEM3-GC31-MM is much larger. In region Ⅱ, wind speed simulated by three models is projected to decrease, but the wind speed from HadGEM3-GC31-MM in region Ⅲ and modeled wind speed in region Ⅳ from NorESM2-MM would climb with the slope equals 0.0001 and 0.0012 respectively. This study indicates that the CMIP6 models have certain limitations to perform realistic wind changes, but CMIP6 could provide available reference for the projection of wind in specific areas.